A Novel Bifunctional Self‐Stabilized Strategy Enabling 4.6 V LiCoO2 with Excellent Long‐Term Cyclability and High‐Rate Capability. Issue 12 (24th April 2019) - Wang, Longlong; Ma, Jun; Wang, Chen; Yu, Xinrun; Liu, Ru; Jiang, Feng; Sun, Xingwei; Du, Aobing; Zhou, Xinhong; Cui, Guanglei
Abstract: Although the theoretical specific capacity of LiCoO2 is as high as 274 mAh g −1, the superior electrochemical performances of LiCoO2 can be barely achieved due to the issues of severe structure destruction and LiCoO2 /electrolyte interface side reactions when the upper cutoff voltage exceeds 4.5 V. Here, a bifunctional self‐stabilized strategy involving Al+Ti bulk codoping and gradient surface Mg doping is first proposed to synchronously enhance the high‐voltage (4.6 V) performances of LiCoO2 . The comodified LiCoO2 (CMLCO) shows an initial discharge capacity of 224.9 mAh g −1 and 78% capacity retention after 200 cycles between 3.0 and 4.6 V. Excitingly, the CMLCO also exhibits a specific capacity of up to 142 mAh g −1 even at 10 C. Moreover, the long‐term cyclability of CMLCO/mesocarbon microbeads full cells is also enhanced significantly even at high temperature of 60 °C. The synergistic effects of this bifunctional self‐stabilized strategy on structural reversibility and interfacial stability are demonstrated by investigating the phase transitions and interface characteristics of cycled LiCoO2 . This work will be a milestone breakthrough in the development of high‐voltage LiCoO2 . It will also present an instructive contribution for resolving the big structural and interfacial challenges in other high‐energy‐density rechargeable batteries. Abstract : A bifunctional self‐stabilized strategy involving Al+Ti bulk codoping and gradient surface Mg doping is first proposed to synchronously enhance the high‐voltage (4.6 V) performances of LiCoO2 . The comodified LiCoO2 shows excellent long‐term cyclability and high‐rate capability in both half and full cells even at high temperature of 60 °C.